Saúde da população “trans”: uma revisão sistemática da produção teórica brasileira - Raimondi, Gustavo Antonio (2016)
This dissertation analyzed the existing work on travestility and transsexuality whose problematic research focused on issues related to health and / or health services. For this purpose, a Literature Review Systematized Descriptive in virtual databases was performed: Bank of Higher Education Personnel Improvement Coordination Thesis (CAPES), Brazilian Digital Library of Theses and Dissertations (BDTD), Scielo and PubMed, between the years 1997 and 2014 in Brazil. We used the search terms "transsexual," "transvestite" and "transgender", each associated with the search term "health", in Portuguese and English. Complementing this search, we used the Documentary Analysis methodology to assess pamphlets productions, institutional documents and non-governmental organizations (NGOs), which were incorporated into the discussion. 295 papers were identified, among theses, dissertations and scientific articles. Of these, 223 were excluded and 72 selected for analysis. Thus, it obtained five theses and dissertations 21 on the topic of travestility and 7 theses and dissertations 9 that deal with transsexuality. Among the selected papers, 16 deal with transsexuality and health, 5 address the issue of travestility and health and work, 9 refer to the term "transgender" and "health". Even though it is an emerging field of research, there is an apparent deviation of the speech, previously anchored in questions whose topics are related to confrontation, infection or illness by HIV / AIDS (level of specialized care) for discussions on the health care for transsexuals in the process (level of specialized care). Still, few papers have specific trans attention in primary care associated with a comprehensive health care, with the empowerment of individuals, respecting the power of life, which are configured as important issues for the Public Policy on Health today.